PERAN ORANG TUA DALAM MEMBANTU MENGEMBANGKAN KARAKTER ANAK DI SMP MUHAMMADIYAH 6 PADANG - Sebriyanti, Betti; Syarif, Mellyarti; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
The problem in this research is about how parents` role can develop students` character in SMP Muhammadiyah 6 Padang. The purpose of this research is having data about parents` role in helping children to develop students` sharacter, like : understanding other people`s feeling. Setting up their mind â wish I can be like him/her â, supporting other opinion, no negative thinking, having good principle of life, being unselfish person, not comparing others, being able to restrain angerness, having scheduled activities, following the voice of goodness and refusing the badness. This kind of research can be called as quantitative description. The source that this research used is primary and secondary data. The population of this research is all of the students from VII, VIII, IX of SMP Muhammadiyah 6 Padang. In collecting the data the researcher uses Taro Yamane formula that is about Â 75 students. The technique in collecting the data is using questionare. The data analysis used by this research is percentageformula. After all of data has been analysed, there will be the result that parents` role in helping the development of students`character of SMP Muhammadiyah 6 Padang has somepoints. 1) Parents` role can help students in achieving a better empathy attitude. 2) Parents` role can help students in achieving a better heartfelt sympathy. 3) Parents` role can help in controlling theirself. Based on the result above, it is hoped that parents and counseling teachers may increase their role to help students in developing the students` character and give the understanding about the good thing they should do so they may have the stronger character than before.